Hypnosis Intervention for Sleep Disturbance: Determination of Optimal Dose and Method of Delivery for Postmenopausal Women. Issue 3 (3rd July 2021) - Elkins, Gary; Otte, Julie; Carpenter, Janet S.; Roberts, Lynae; Jackson, Lea' S.; Kekecs, Zoltan; Patterson, Vicki; Keith, Timothy Z.
ABSTRACT: Sleep disturbances are a pervasive problem among postmenopausal women, with an estimated 40 to 64% reporting poor sleep. Hypnosis is a promising intervention for sleep disturbances. This study examined optimal dose and delivery for a manualized hypnosis intervention to improve sleep. Ninety postmenopausal women with poor sleep were randomized to 1 of 4 interventions: 5 in-person, 3 in-person, 5 phone, or 3 phone contacts. All received hypnosis audio recordings, with instructions for daily practice for 5 weeks. Feasibility measures included treatment satisfaction ratings and practice adherence. Sleep outcomes were sleep quality, objective and subjective duration, and bothersomeness of poor sleep. Results showed high treatment satisfaction, adherence, and clinically meaningful (≥ 0.5 SD ) sleep improvement for all groups. Sleep quality significantly improved, p < .05, η2 = .70, with no significant differences between groups, with similar results for the other sleep outcomes across all treatment arms. Comparable results between phone and in-person groups suggest that a unique "dose" and delivery strategy is highly feasible and can have clinically meaningful impact. This study provides pilot evidence that an innovative hypnosis intervention for sleep (5 phone contacts with home practice) reduces the burden on participants while achieving maximum treatment benefit.